Dispersive solid phase extraction of chlorophenols using carbon-coated magnetic nanoparticles. Issue 3 (3rd July 2019) - Iqbal, Mehwish; Shah, Jasmin; Jan, Muhammad Rasul; Zeeshan, Muhammad
Abstract: Carbon-coated magnetic nanoparticles were modified with cationic surfactant and used for the dispersive solid phase extraction of chlorophenols from aqueous samples. Surfactant adsorbed on the surface of the nanoparticles resulted in mixed hemimicelles for high extraction efficiency of chlorophenols. Under optimized conditions, calibration curves were linear from 0.5–20 mg L −1 for analytes with limit of detection between 0.2 and 0.4 mg L −1 . The method was applied to extraction of chlorophenols from tap water, well water and industrial effluent. Recoveries were in the range of 94.0–99.4%, suggesting that sample matrix had little effect on the yields of extraction.